2019
DOI: 10.1016/j.scriptamat.2019.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation process preventing thermal embrittlement of a Zr-Cu-Fe-Al bulk metallic glass

Abstract: The structural changes and mechanical properties of Zr63Cu22Fe5Al10 bulk metallic glass (BMG), and a Zr63Cu27Al10 glass made for comparison, were studied on annealing below the crystallization temperature. The phase composition of the samples was studied by conventional X-ray diffractometry and high-resolution transmission electron microscopy including the atomic-scale elemental mapping. The samples were mechanically tested in compression. The Zr63Cu22Fe5Al10 bulk metallic glass shows high strength and good de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…This discrepancy may be explained by the following. In a previous investigation, it was observed that in an annealed Zr-Cr-Fe-Al BMG, secondary shear bands were localized in the vicinity of a dominant shear band after compression testing [52]. The above result was in contrast with the as-cast sample, where the shear bands were more widely distributed within the sample.…”
Section: Discussionmentioning
confidence: 86%
“…This discrepancy may be explained by the following. In a previous investigation, it was observed that in an annealed Zr-Cr-Fe-Al BMG, secondary shear bands were localized in the vicinity of a dominant shear band after compression testing [52]. The above result was in contrast with the as-cast sample, where the shear bands were more widely distributed within the sample.…”
Section: Discussionmentioning
confidence: 86%
“…6. This alloy system consists of atom pairs with a small positive heat of mixing in the liquid state: and Cu-Fe (+ 13 kJ mol -1 [48]) and Cu-Co (+ 6 kJ mol -1 [49]).…”
Section: Crystallization Temperature and Phase Separation In The Solid And Liquid Statementioning
confidence: 99%
“…However, practical application of BMGs have been hindered in many cases, owing to their inhomogeneous plastic deformation 4,5 . To tackle this challenge, several methods such as chemical composition tuning, composite making or rejuvenating processes have been proposed [6][7][8][9][10] . Among them, rejuvenation process is an applicative technique, in which structural atomic excitation occurs and glassy material moves to higher energy state [11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%